The Role Of Taruna Tani In Supporting Organic Agriculture (Case Study Of Gentungan Village, Mojogedang District, Karanganyar Regency) - Anisya Oktaviana; Retno Setyowati; Eksa Rusdiyana (UNIVED Press, Dehasen University Bengkulu, 2024)
Purpose: This study aims to analyze the roles, efforts, supporting factors, and obstacles of the youth farmer group (taruna tani) in supporting organic farming in Gentungan Village, Mojogedang District, Karanganyar Regency. Methodology: The research employed a qualitative descriptive method with purposive sampling for location selection. Informants were determined using purposive and snowball techniques, involving 15 individuals. Data were collected through observation, in-depth interviews, and documentation, and analyzed using Miles and Huberman’s approach. Results: The youth farmer group plays roles as family members, community members, and contributors to agricultural development. Findings: Efforts include fostering entrepreneurship through the production and sale of organic fertilizers and rice, and agribusiness skill training facilitated by stakeholders. Originality and Novelty: The youth farmer group demonstrates a significant role in advancing organic farming in the village. Conclusion: Supporting factors include self-awareness, organizational structure, government and mentor support, and shared interests. Obstacles include peer influence and members’ main job commitments. Type of Paper: Empirical research article.